Escale. - Pijaudier, Joëlle (Villeneuve d'Ascq : Musée d'Art Moderne, 1993)
De Bruyckere, Berlinde ; Blaussyld, Maurice ; Boulanger, Christophe ; DC, Franky ; De Busschère, Alec ; Deknuydt, Christine ; Dumont, Bruno ; El Baz, Mohamed ; Eyberg, Sylvie ; Fenzy, Rémy ; Gussin, Graham ; Hamlyn, Jim ; Jackson, Mel ; Kovats, Tania ; Lebret, Patrick ; Mistiaen, Carlo ; Richardson, Craig ; Timoney, Padraig ; Wor, Frédéric
Escale / Stopover / Tussenstop, Musée d'Art Moderne, Villeneuve d'Ascq, 6 novembre 1993 - 9 janvier 1994
Frans & Engels & Nederlands
kunstcatalogus